2003
DOI: 10.2169/internalmedicine.42.72
|View full text |Cite
|
Sign up to set email alerts
|

Nephrotic Syndrome Due to Primary AL Amyloidosis, Successfully Treated with VAD and Subsequent High-dose Melphalan Followed by Autologous Peripheral Blood Stem Cell Transplantation.

Abstract: Primary ALamyloidosis involves vital organs from the early phase of illness, resulting in a poor prognosis. We report a patient with nephrotic syndrome due to this type

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 24 publications
0
18
0
1
Order By: Relevance
“…The combination of VAD and HDM for treatment of AL amyloidosis with nephrotic syndrome has been shown to be feasible in one patient with nephrotic syndrome (Sezer et al, 1999) and in reports on small cohorts (van Gameren et al, 2002;Gono et al, 2003). However, data on toxicity and efficacy of VAD chemotherapy prior to HDM and ASCT are limited in patients with AL amyloidosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The combination of VAD and HDM for treatment of AL amyloidosis with nephrotic syndrome has been shown to be feasible in one patient with nephrotic syndrome (Sezer et al, 1999) and in reports on small cohorts (van Gameren et al, 2002;Gono et al, 2003). However, data on toxicity and efficacy of VAD chemotherapy prior to HDM and ASCT are limited in patients with AL amyloidosis.…”
Section: Discussionmentioning
confidence: 99%
“…They demonstrated a significantly better survival rate for the group of patients treated with HDM chemotherapy (Dispenzieri et al, 2004). The use of additional induction chemotherapy prior to HDM has been evaluated in a few studies to date (Sezer et al, 1999;van Gameren et al, 2002;Gono et al, 2003). New regimens, including induction chemotherapy prior to HDM need to be tested in order to assess whether the results of this regimen can be improved in terms of toxicity and efficacy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…S o l i d l i n e : t h e r e mi s s i o n g r o u p ( n = 4 ) , b r o k e n l i n e : t h e n o n -r e mi s s i o n g r o u p ( n = 4 ) . Ce n s o r e d p a t i e n t s a r e t i c k e d a l o n g t h e s u r v i v a l c u r v (6)(7)(8)13). Several recent reports have demonstrated that some patients with primary systemic AL amyloidosis show good therapeutic outcomes after cyclic administration of VAD alone (5,14).…”
Section: Therapeutic Outcomesmentioning
confidence: 99%
“…Details of the intensive chemotherapy are described elsewhere (11,12). Briefly, stem cells were collected using etoposide and granulocyte-colony stimulating factor after 2 courses of VAD as an induction treatment, and high-dose melphalan was administered intravenously at 140 mg/m 2 total dose over 2 days.…”
Section: Treatmentmentioning
confidence: 99%